Gitasanti Sebagai Terapi Yoga Di Pasantian Dharma Usada Desa Adat Ubud - Yuliari, Sang Ayu Made; Seniwati, Desak Nyoman; Sari, Ida Ayu Putu (Jurnal Penelitian Agama Hindu, 2023)
Dharmagita activities, which is better known in the community as meshanti, are one form of offerings through singing sacred songs. Sacred song is one type of the five types of songs in Hinduism which are known as pancagita. Meshanti is also a form of yoga and closely related to catur marga yoga which is performed through yajna ceremonies. The aim of the research is to identify the implementation, the procedure, and benefit of using gitashanti as a yoga therapy. The present study was conducted with qualitative method and the data were collected using observation, interview, literature study, and documentation. The present study found that 1) Gitashanti is performed as a yoga therapy in Pasantian Dharma Usada since in its implementation it uses the action of ngunda napas (breathing regulation) and ngandet angkihan (holding breath). In yoga, the action of regulating breath is called pranayama and the sitting pose is called asana. For the female, the sitting pose is kneeling (bajrasana) and the male sitting pose is sitting cross-legged (ardha padmasana). 2) The procedure starts with worshipping the Goddess Saraswati. 3) The benefits are a) health benefits, the participants enjoyed a significant blood pressure decrease with the average of 33.3mmHg after joining gitashanti, ngayah (charity service)/community social activities/ menyama braya (familial activities), c) preserving Balinese culture trough nyastra (literary activities).